2023
DOI: 10.33963/kp.a2022.0260
|View full text |Cite
|
Sign up to set email alerts
|

Managed Care after Acute Myocardial Infarction (MC-AMI) — Poland’s nationwide program of comprehensive post-MI care improves prognosis in 2-year follow-up. A single high-volume center intention-to-treat analysis

Abstract: Background: Managed Care in Acute Myocardial Infarction (MC-AMI) is a program introduced in Poland aimed at comprehensive, scheduled, and supervised care for AMI patients to improve longterm prognosis.Aims: Our study aimed to compare 24-month mortality and the incidence of major cardiovascular events (MACE: a composite of death, recurrent MI, and hospitalization for heart failure) in a cohort of AMI patients treated in the MC-AMI era (intention-to-treat analysis) vs. similar population treated before the MC-AM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…It is also worth mentioning that in this study [14] AMI was not diagnosed using the latest universal definition of MI. In addition, the dataset is missing some variables, including socioeconomic and behavioral risk factors, which could potentially affect both enrollment and compliance.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…It is also worth mentioning that in this study [14] AMI was not diagnosed using the latest universal definition of MI. In addition, the dataset is missing some variables, including socioeconomic and behavioral risk factors, which could potentially affect both enrollment and compliance.…”
mentioning
confidence: 84%
“…Notably, differences were seen as soon as 3 months following intervention. In this current publication, Kułach et al [14] compared the 24-month mortality rates and incidence of major adverse cardiovascular events (MACE: a composite of death, recurrent MI, and hospitalization for heart failure) in a cohort of AMI patients treated in the MC-AMI era (intention-to-treat analysis) vs. similar population treated before the MC-AMI era. The investigators analyzed 2323 consecutive patients with AMI: 1261 patients enrolled in the MC-AMI era (study group) and 1062 patients treated 12 months before the MC-AMI era (control).…”
mentioning
confidence: 99%
“…Cardiac rehabilitation is carried out by an interdisciplinary team enabling a holistic approach to the patient, and, consequently, dietary and psychological education is also present. The MC-AMI programme, which has been in operation for more than six years continuously, has undeniable clinical and economic benefits, which have been confirmed by numerous research studies showing short-term benefits as well as those from longer-term (12-month, 24-month) follow-up [4,6,9,[14][15][16][17][18][19]. Those studies focused on a range of variables that affect observed outcomes, which, in turn, become drivers to further improve the system and introduce tools to further motivate patients.…”
Section: Introductionmentioning
confidence: 91%
“…Revascularisation procedures are carried out in cardiac catheter laboratories that provide 24 h haemodynamic emergency services. In Poland, there is a network of 160 interventional cardiology centres, performing 735 percutaneous coronary interventions per million inhabitants [5,6]. These advanced methods of diagnosis and treatment have resulted in a significant reduction in early adverse events, including in-hospital deaths in the acute phase of myocardial infarction [7].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, dietary and psychological education is provided. The programme has continued to the present day with studies showing its significant clinical benefits [7,[21][22][23][24][25][26][27][28].…”
Section: The Role Of Primary Prevention and Secondary Prevention In I...mentioning
confidence: 99%